2011
DOI: 10.1126/science.1211908
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inositol Pyrophosphates on Cellular Energy Dynamics

Abstract: With its high-energy phosphate bonds, adenosine triphosphate (ATP) is the main intracellular energy carrier. It also functions in most signaling pathways, as a phosphate donor or a precursor for cyclic adenosine monophosphate. We show here that inositol pyrophosphates participate in the control of intracellular ATP concentration. Yeasts devoid of inositol pyrophosphates have dysfunctional mitochondria but, paradoxically, contain four times as much ATP because of increased glycolysis. We demonstrate that inosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
260
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 221 publications
(273 citation statements)
references
References 36 publications
8
260
0
Order By: Relevance
“…Consistently, knockdown of IP6K1 in cultured hippocampal neurons augmented action potential-driven synaptic vesicle exocytosis at synapses. Using a FRET-based in vitro vesicle fusion assay, we found that 5-IP 7 , but not 1-IP 7 , exhibited significantly higher inhibitory activity toward synaptic vesicle exocytosis than IP 6 . Synaptotagmin 1 (Syt1), a Ca 2+ sensor essential for synaptic membrane fusion, was identified as a molecular target of 5-IP 7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, knockdown of IP6K1 in cultured hippocampal neurons augmented action potential-driven synaptic vesicle exocytosis at synapses. Using a FRET-based in vitro vesicle fusion assay, we found that 5-IP 7 , but not 1-IP 7 , exhibited significantly higher inhibitory activity toward synaptic vesicle exocytosis than IP 6 . Synaptotagmin 1 (Syt1), a Ca 2+ sensor essential for synaptic membrane fusion, was identified as a molecular target of 5-IP 7 .…”
mentioning
confidence: 99%
“…We report here that elevated 5-IP 7 levels, caused by overexpression of inositol hexakisphosphate (IP 6 ) kinase 1 (IP6K1), suppressed depolarization-induced neurotransmitter release from PC12 cells. Conversely, IP6K1 depletion decreased intracellular 5-IP 7 concentrations, leading to increased neurotransmitter release. Consistently, knockdown of IP6K1 in cultured hippocampal neurons augmented action potential-driven synaptic vesicle exocytosis at synapses.…”
mentioning
confidence: 99%
“…Inositol pyrophosphates have gained recent attention as signaling molecules in amoeba, yeast, and mammalian cells (Mulugu et al, 2007;Shears, 2009;Chakraborty et al, 2011;Szijgyarto et al, 2011;Wundenberg and Mayr, 2012;Pöhlmann et al, 2014). Here, we describe the presence of InsP 7 and InsP 8 in the model plant Arabidopsis and show that VIH2 is a functional inositol pyrophosphate synthetase responsible for InsP 8 production, playing a critical role in jasmonate-regulated defenses.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, the level of polyP is metabolically connected to the level of inositol pyrophosphates (17). These molecules (InsP 7 and InsP 8 ) are notable for their ability to control cellular ATP synthesis (32,33). Because polyP influences the level of ATP in vegetatively growing cells (Fig.…”
Section: Altered Atp and Accumulation Of Inositol Pyrophosphates In Pmentioning
confidence: 99%